FY2019 Costa Rica Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2019)
The country opinion survey in Costa Rica assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Costa Rica perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral and bilateral agencies, media, academia, the private sector, and civil society in Costa Rica on: (1) their views regarding the general environment in Costa Rica; (2) their overall attitudes toward the WBG in Costa Rica; (3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Costa Rica; and (4) their perceptions of the WBG’s future role in Costa Rica.